Diosgenin: Mechanistic Insights on its Anti-inflammatory Effects - Karami-Mohajeri, Somayyeh; Mohammadinejad, Reza; Ashrafizadeh, Milad; Mohamadi, Neda; Mohajeri, Mohammad; Sharififar, Fariba (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2022)
Diosgenin (DG), a well-known steroid saponin, has shown anti-inflammatory effects. This review was aimed to discuss all published literature concerning the anti-inflammatory effects of diosgenin. Based on the modulatory impact of DG on the NF-ΚB pathway, its supplementation is associated with downregulation of the NF-ΚB pathway and TGF-β, resulting in inhibition of inflammation. It appears that upstream modulators of NF-ΚB signaling pathways such as Tlrs and downstream mediators include iNOS and COX-2, leading to the inhibition of the inflammatory response and development of pathological conditions. Due to the low toxicity of the herbal compounds, the risk of the side effects of DG use for the management of inflammatory disorders such as asthma, rheumatism, rhinitis, and arthritis is lower than that of synthetic glucocorticoids. It has been shown that regulation of NF-ΚB and oxidative stress signaling pathways by DG is beneficial against cardiotoxicity induced by chemotherapeutic agents such as doxorubicin.
Keywords: Phytosterol